The effect of chewing gum's flavor on salivary flow rate and pH - Maryam Karami-Nogourani; Raha Kowsari-Isfahan; Mozhgan Hosseini-Beheshti (Wolters Kluwer Medknow Publications, 2011)
Background: Chewing sugar-free gums is a convenient way to increase salivary flow. Salivary flow increases in response to both gustatory (taste) and mechanical (chewing) stimuli, and chewing gum can provide both of these stimuli. The aim of this study was to compare the effect of five different flavors of sugar-free chewing gum on the salivary flow rate (SFR) and pH. Materials and Methods: Fifteen dental students volunteered at the same time on six consecutive days, to collect one minute unstimulated saliva. After five minutes, while some volunteers continued to collect only unstimulated saliva, the others asked to start chewing one of the five flavored gums randomly. The flavors were spearmint, cinnamon, watermelon, strawberry, and apple. The whole saliva was collected over time periods of 0 - 1, 1 - 3, and 3 - 6 minutes, and the SFR and pH were also measured. The data were subjected to pair t-test, repeated-measures analysis of variance, and Duncan tests. Results: Compared to the unstimulated rate, all five different flavored gums significantly increased the SFR within six minutes. Although the flow rate peaked during the first minute of stimulation with all five products, it reduced gradually, but still remained above the unstimulated saliva, after six minutes. In the first minute, the strawberry-flavored gums showed the highest weight, yet, it only induced a significantly higher SFR compared to the cinnamon-flavored gums. During one to three minutes, strawberry and apple-flavored gums showed significantly higher SFR, respectively, compared to cinnamon-flavored gums. There were no significant differences in the flow rates elicited by each flavored gum through the three-to-six minute interval, although the spearmint-flavored gums induced slightly higher SFR. Only the spearmint and cinnamon-flavored gum significantly increased the salivary pH. Conclusion: Gum flavor can affect the SFR and special flavors may be advised for different individuals according to their oral conditions.